Assessing Air Quality, Climate Change, and Migration Dynamics in Delhi NCR: A System Dynamics Approach - Ayushi Singh; Irfanullah Khan (Recent Trends in Mathematics, 2025)
As climate change accelerates and environmental degradation worsens, urban centers like Delhi NCR are under increasing pressure from internal migration. Poor air quality—especially in rural and peri-urban regions—emerges both as a driver of out-migration and a deterrent for in-migration to already burdened cities. This study develops a system dynamics (SD) model that integrates climate variables, air pollution metrics, economic indicators, governance quality, and migration behavior to simulate population flows into the Delhi NCR region. The model reveals critical feedback loops among air quality, public health, labor dynamics, and migration incentives. Drawing on national climate projections, air quality indices, and migration data, the model forecasts scenarios through 2060 and evaluates the impact of policy interventions, including emissions control, urban reforms, and rural aid. Findings show that, without decisive action, Delhi NCR could face unsustainable migration, heightened health risks, and worsening urban stress. The research calls for integrated policy frameworks that align climate adaptation, public health, and migration governance in India’s most densely populated region. Beyond forecasting population pressures, the study highlights the broader socio-economic implications of unchecked climate-driven migration. Rising health costs from air-pollution-related diseases, coupled with declining labor productivity, may weaken the region’s economic competitiveness and exacerbate inequalities. Migrant populations—often employed in informal sectors—are particularly vulnerable to inadequate housing, limited healthcare access, and unstable livelihoods, thereby amplifying cycles of poverty and environmental stress. Moreover, unplanned migration could overwhelm existing infrastructure, strain public services, and fuel social tensions between resident and migrant communities. By using the SD model as a decision-support tool, policymakers can test the long-term consequences of different strategies, from aggressive emissions reduction to investments in rural resilience that reduce migration push factors. Ultimately, the study underscores that migration in the climate era is not merely a demographic challenge but a governance test requiring cross-sectoral coordination, forward-looking planning, and a commitment to environmental justice.
Keywords: Air quality; Climate change; Internal migration; System dynamics; unsustainable migration